2011
DOI: 10.3390/cryst1040244
|View full text |Cite
|
Sign up to set email alerts
|

Defect Scheelite-Type Lanthanoid(III) Ortho-Oxomolybdates(VI) Ln0.667[MoO4] (Ln = Ce, Pr, Nd, and Sm) and Their Relationship to Zircon and the NaTl-Type Structure

Abstract: The rare-earth metal(III) ortho-oxomolybdates with the formula Ln 0.667 [MoO 4 ] (Ln = Ce, Pr, Nd, and Sm) and defect scheelite-type structure crystallize in the tetragonal space group I4 1 /a (a = 533-525, c = 1183-1158 pm) with four formula units per unit cell. The Ln cation is situated at the 4a position. Due to this equal site multiplicity, the lanthanoid(III) cations have to be statistically under-occupied to maintain electroneutrality, thus a defect scheelite structure emerges. The partial structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Redox processes between Ce 3+ and Mo 6+ were never observed, neither in syntheses of chloride derivatives of cerium oxidomolybdates4 nor in cerium oxidomolybdates of various compositions, e.g. Ce 2 Mo 2 O 9 14. Bond valence calculations15,16 for the title compounds support this statement providing values of +3 (±0.1) and +6 (±0.1) for the valences of the cerium and the molybdenum cations, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…Redox processes between Ce 3+ and Mo 6+ were never observed, neither in syntheses of chloride derivatives of cerium oxidomolybdates4 nor in cerium oxidomolybdates of various compositions, e.g. Ce 2 Mo 2 O 9 14. Bond valence calculations15,16 for the title compounds support this statement providing values of +3 (±0.1) and +6 (±0.1) for the valences of the cerium and the molybdenum cations, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…16 For either application, as a dielectric material or for the immobilization of nuclear waste, the efficacy of the material will depend on its stability. Material stability is again related to material properties such as crystallinity, phase purity, and distribution of the luminescent probe, 9 or radionuclide, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although dipolar interactions appear to be more classical than their exchange-coupled counterparts, it has been shown that on a square or diamond lattice, quantum fluctuations can map long-ranged dipolar interactions to a two-dimensional Ising model [5][6][7]. The LiRF 4 family is special as the rare-earth ions are arranged in a slightly distorted diamond-like structure making them intriguing to study in relation to order by disorder phenomena [8].For the case of a dipolar-coupled Ising ferromagnet, the theoretical upper critical dimension D * = 3 and the mean-field calculations actually apply quite well as shown, for instance, in LiHoF 4 [9]. This is despite the significant role of hyperfine interactions around the quantum phase transition [10,11].…”
mentioning
confidence: 99%
“…Although dipolar interactions appear to be more classical than their exchange-coupled counterparts, it has been shown that on a square or diamond lattice, quantum fluctuations can map long-ranged dipolar interactions to a two-dimensional Ising model [5][6][7]. The LiRF 4 family is special as the rare-earth ions are arranged in a slightly distorted diamond-like structure making them intriguing to study in relation to order by disorder phenomena [8].…”
mentioning
confidence: 99%